Cinebot: more than just a robot, a laboratory - Tacuri, Andrés; Villamagua, Luis; Lapo, Pablo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This work reports the design, construction and deployment of a mechatronic system, which, combined with a computer vision module, provides students and teachers with a tool to experience with concepts of kinematics of a particle throughout the usage of a robot, known as to Cinebot, which can be controlled from any smart device endowed with a stable internet connection. The methodology used for envisioning and developing the system was engineering design. The figure of merits of the prototype was evaluated under a linear motion scheme with constant speed (~0.10 m/s), showing errors between 0.08 and 3.2%.